Brain Renin–Angiotensin System at the Intersect of Physical and Cognitive Frailty - Cosarderelioglu, Caglar; Nidadavolu, Lolita S.; George, Claudene J.; Oh, Esther S.; Bennett, David A.; Walston, Jeremy D.; Abadir, Peter M. (Frontiers in Neuroscience, 2020)
The renin-angiotensin system (RAS) was initially considered to be part of the endocrine system regulating water and electrolyte balance, systemic vascular resistance, blood pressure, and cardiovascular homeostasis. It was later discovered that intracrine and local forms of RAS exist in the brain apart from the endocrine RAS. This brain-specific RAS plays essential roles in brain homeostasis by acting mainly through four angiotensin receptor subtypes; AT1R, AT2R, MasR, and AT4R. These receptors have opposing effects; AT1R promotes vasoconstriction, proliferation, inflammation, and oxidative stress while AT2R and MasR counteract the effects of AT1R. AT4R is critical for dopamine and acetylcholine release and mediates learning and memory consolidation. Consequently, aging-associated dysregulation of the angiotensin receptor subtypes may lead to adverse clinical outcomes such as Alzheimer’s disease and frailty via excessive oxidative stress, neuroinflammation, endothelial dysfunction, microglial polarization, and alterations in neurotransmitter secretion. In this article, we review the brain RAS from this standpoint. After discussing the functions of individual brain RAS components and their intracellular and intracranial locations, we focus on the relationships among brain RAS, aging, frailty, and specific neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and vascular cognitive impairment, through oxidative stress, neuroinflammation, and vascular dysfunction. Finally, we discuss the effects of RAS-modulating drugs on the brain RAS and their use in novel treatment approaches.